Residual state ownership and stock market integration: evidence from Chinese partly privatised firms - Li, Hong (Elsevier, 2018)
This paper assesses China’s integration with the global stock market over its privatisation process, by examining the asset pricing mechanisms of Chinese firms under different levels of state ownership within a two-beta CAPM framework. We derive time-varying national and global systematic risks for the portfolios compiled on the basis of residual state ownership and examine how these risks are priced while controlling for structural changes exogenously and endogenously. Through anchoring our analysis to the portfolios capturing this institutional factor, we observe mostly positive pricing of the systematic risks, instead of the negative pricing often found in the literature on emerging markets. Within this well-controlled framework, some interesting points emerge. While full privatisation does not eliminate exposure to the national systematic risk, more heavily privatised firms (i.e., those with the least residual state ownership) tend to price only the global risk more often than less privatised ones. Hence, among partly-privatised firms, integration with the global market strengthens as state ownership decreases. These results suggest that emerging economies pursue rigorous privatisation and yet governments keep small stakes in privatised firms in order to ensure integration with the global market.